Green Innovation, Environmental Management Accounting, dan Nilai Perusahaan: Mampukah Reputasi Perusahaan Berperan Sebagai Pemediasi? - Hellenikapoulos , Maria; Supramono, Supramono (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2024)
Stakeholder demands for firms to operate by paying attention to environmental aspects make firms implement GI and EMA. This can attract investors and increase firm value. This research aim to re-examine the relationship between GI and EMA on firm value and examine the role of firm reputation as mediator. Samples of this study were firms registered on BEI and PROPER in 2019-2022 using purposive sampling. This research used Eviews 12. The results show that GI has positive effect on firm value while EMA has negative effect on firm value. Meanwhile, firm reputation has not proven to mediate the relationship between GI and EMA on firm value.